Prenehanje pogodbe o zaposlitvi na podlagi sodbe sodišča - Kogej Dmitrovič, Biserka (Delavci in delodajalci, 2016)
The article presents the institute of termination of employment contract on the grounds of the court decision. It provides a review of former and a summary of the new regulations with emphasis on the changes. The possibility that the employer too can propose termination of the employment contract is also presented in the article. The issue of what can happen if the worker does not file an application for payment of remuneration is discussed, as are judicial decisions on fixing the date of termination of employment contract. Further, the statutory criteria for the determination of remuneration on the grounds of the court decision on termination of employment contract and the previous case-law are presented.
Keywords: delovna sodišča; pogodba o zaposlitvi; prenehanje; sodna praksa; sodne odločbe